The Impact of Urban Home Gardens on The Mental Well-Being of Women in The Greater Jakarta Area - Benanda Yasminingrat, R Anantama; Sulistyantara, Bambang; Nasrullah, Nizar (Alanya Üniversitesi, 2023)
Promoting positive mental health is of utmost importance, especially in today's urban context, as recognized by the World Health Organization. However, the scarcity of green spaces in urban areas presents challenges for fostering a connection with nature. To address this gap, this study investigates the distinctive contribution of urban home gardens to the mental well-being of women in the Greater Jakarta Area. Through an online survey, participant backgrounds and mental well-being were assessed using the WEMWBS scale. Validity and reliability were established using Pearson's product-moment correlation and Cronbach's alpha, respectively. The study unravels several influential factors, including garden interaction (visit frequency and duration) and size. Crucially, it advances the literature by shedding light on the original contribution of urban home gardens to mental well-being. Notably, women who visit their urban home garden more than seven times a week and spend over two hours per day in their garden report the highest levels of mental well-being. These findings highlight the unique role of urban home gardens in promoting mental well-being among urban women. Consequently, they hold implications for policymakers and practitioners aiming to enhance mental well-being and foster access to green spaces in urban areas.